Fostering Elite Athlete Development and Recreational Sport Participation: a Successful Club Environment - Galatti,Larissa Rafaela (2016)
The overall aim of this article was to present a positive case study about how a sport club can foster both elite athlete development in parallel with offering a diverse range of sport activities to attract and maintain a greater number of children and youth for continued participation in a long term sport program. To this end, an in-depth case study was conducted of a model Spanish Basketball Club, considered an example of success in achieving consistent level of performance and high rates of participation among their youth. Data were collected from in-depth interviews with administrators, setting observation, and analysis of current and archived club documents. The results show that the club has created changes over the years that have led to a clear organizational structure with a philosophy that connects its youth development teams and elite teams. An increase focus on youth development, the addition of recreational activities, and the implementation of a coach education program have been linked to enhanced participation rate and performance.